Multilateral Development Banks as Instruments of EU–Asian Relations - Smolaga, Mateusz (Power Shifts in East Asia and Their Implications for Asia–Europe Relations, 2019)
In January 2016, the People’s Republic of China became the 65th member country of the European Bank for Reconstruction and Development: a multinational financial institution created by the European Union and the European Investment Bank “to promote entrepreneurship and change lives” across the Mediterranean region, Southern, Central and Eastern Europe, the Caucasus and Central Asia. Perhaps Chinese involvement in this European institution could be considered a surprising development, until we realize both the Asian Development Bank and the Asian Infrastructure Investment Bank, which are generally seen as the major players, are constituted of over a dozen EU members. This complexity of relations is also evident throughout the rest of the multilateral development banks active in Asia.The aim of the article is to test the hypothesis that the cooperation between multilateral development banks not only provides the opportunity for the funding of various investment projects crucial to the world economy, but can also facilitate the achievement of the individual political goals of their members.The text offers a brief comparative analysis of the multilateral development banks that operate and interact in Asia, presenting the common ground for their financial cooperation, while attempting to identify ways of avoiding serious conflicts of interest. The real test of this hypothesis must take into account the political context in which these interactions take place.